2006
DOI: 10.1001/archpedi.160.3.302
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Specific Medical Interventions on Reducing the Prevalence of Mental Retardation

Abstract: Although specific medical interventions have prevented thousands of cases of MR, their contribution to the overall prevalence of MR is relatively small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 62 publications
2
31
0
1
Order By: Relevance
“…Even today clinicians perform extensive diagnostic testing on people with cognitive disabilities in hopes of finding a simple medical cure, despite the relatively small impact of PKU and similar conditions on the prevalence of intellectual disability in the late 20th century. 3 In the 1970s and 1980s, PKU took on new roles as an exemplar in the naturenurture debates and as a resource for advocates of genetic testing. 2 PKU is a genetic condition that is highly treatable if infants receive a diagnosis at birth and are placed on a diet low in phenylalanine, an essential amino acid found in all dietary proteins.…”
mentioning
confidence: 99%
“…Even today clinicians perform extensive diagnostic testing on people with cognitive disabilities in hopes of finding a simple medical cure, despite the relatively small impact of PKU and similar conditions on the prevalence of intellectual disability in the late 20th century. 3 In the 1970s and 1980s, PKU took on new roles as an exemplar in the naturenurture debates and as a resource for advocates of genetic testing. 2 PKU is a genetic condition that is highly treatable if infants receive a diagnosis at birth and are placed on a diet low in phenylalanine, an essential amino acid found in all dietary proteins.…”
mentioning
confidence: 99%
“…Nonetheless, our study revealed that, among the medical technologies introduced between 1950 and 2000, NICU treatment of LBW infants is the most significant contributor to the increased prevalence of ID. In the first third of the 20th century, the predominant causes of ID were infections and metabolic conditions, 12 and infant mortality was greater than 100 deaths per 1000 live births. 26 By 1960, overall infant mortality dropped to 23.3 per 1000, yet remained high for LBW infants, ranging from 899.1 for birth weights of 500 to 999 g to 61.0 for 2000 to 2499 g. 20 Since 1960, infant mortality rates have declined for all groups, most dramatically for the smallest infants, while the number of LBW infants has increased.…”
Section: Discussionmentioning
confidence: 99%
“…Such programs likely had less effect on the prevalence of intellectual disability than did more general children's and maternal health programs, however. 54 This is because most cases of intellectual disability are related to a combination of risk factors, such as family income, technology available, within the funding and priorities set by Congress and the president. Federal children's health programs are but one factor in determining children's health in the United States, of course, but all efforts to improve children's health over the past century have faced the same enduring set of historical circumstances.…”
Section: Discussionmentioning
confidence: 99%